(untitled) (TAMADDUN NURI JURNALI, 2025)
This article discusses the importance of studying the specific terminology and terms of the English language in the field of agronomy, its scientific and practical aspects. Terminological units play an important role in scientific research in agronomy, innovative technologies and solving global agricultural problems, therefore, detailed information is provided about the need to study these terms.